Pengaruh Rekrutmen Terhadap Kinerja Karyawan Pada PT. Bina Mitra Swasembada di Jakarta Selatan - Yuli Wahyudi (Peneliti.net, 2023)
This study aims to determine the effect of recruitment on employee performance at PT Bina Mitra Swasembada in South Jakarta. The method used is explanatory research with a sample of 77 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study on the recruitment variable obtained an average score of 3.79 with good criteria. Employee performance variable obtained an average score of 3.89 with good criteria. Recruitment has a significant effect on employee performance with the regression equation Y = 14.822 + 0.637X, and a correlation value of 0.743 or strong with a determination of 55.2%. The hypothesis test obtained a significance of 0.000 <0.05.